Highly sensitive sequence specific qPCR detection of Mycobacterium tuberculosis complex in respiratory specimens. (December 2016) - Reed, Jennifer L.; Walker, Zachary J.; Basu, Debby; Allen, Veronica; Nicol, Mark P.; Kelso, David M.; McFall, Sally M.
Summary: Nucleic acid amplification tests for Mycobacterium tuberculosis (MTB) detection from sputum are highly sensitive and specific with smear microscopy positive specimens, but their sensitivity with smear-negative/culture-positive specimens is much lower; therefore, these tests cannot rule out a tuberculosis diagnosis. Co-extraction of PCR inhibitors may be a cause of decreased test sensitivity. Here the design and early validation of a MTB screening assay with sample preparation and qPCR methods designed to specifically address this diagnostic gap is reported. First, human genomic DNA is identified as a significant qPCR inhibitor. To circumvent this problem, a novel, streamlined sample preparation method utilizing detergent and proteolysis to thin the sputum and DNA sequence specific MTB DNA isolation was developed. Additionally, a multiplexed qPCR assay targeting two MTB complex-specific loci: the potentially multi-copy IS 6110 and the single-copy senX3-regX3, combined with the cotJC gene from Bacillus atrophaeus spores amplified as a process control was developed . The limit of detection of the test was estimated to be 20 cfu/ml which is significantly lower than the Xpert ® MTB/RIF assay. In a preliminary field study of 60 de-identified blinded sputa, a test sensitivity of 96% and specificity of 100% was observed when compared to the Xpert ® MTB/RIF assay.